Symmetrical analysis and evaluation of Differential Resistive Sensor output with GSM/GPRS network - Abdulwahab, Deji; Khan, Sheroz; Chebil, Jalel; Alam, A. H. M. Zahirul (2011)
Differential Resistive Sensor Interface is industrially significant for GSM/GPRS transmission to a mobile phone in order to enhance communication technique. The Sensor output needs to be made digital, hence the need for a microcontroller and the signal is displayed in a PC as output voltage, sensed parameter, x. A frequency and voltage output are obtained, showing how a small change in differential value of the resistor can bring galloping effect on the signal path. This transducer comprises diodes, resistors, capacitor and 555 Timer, that would produce an analog output, which is then converted to digital by the use of a microcontroller. Thus, at this stage, the output signal would then be interfaced with a GSM/GPRS modem called KLS-RUP-200-Pms3-300 module to be received by cellular mobile phone. The errors and the non-linear path of the transducer response curve are compensated for at the output stage. At various stages, different codes are written for the interfacing process. Analysis of the resulting signal is done using various engineering software such as Matlab, Orcad Pspice, GUI etc. The device also finds applications in areas of liquid level characterization, sensing the bent in a bimetallic strip also detects the expansion and contraction of the muscles. PIC16F877 is used which has the capability of monitoring up to 8 analog channels (from the Sensor/Transducer) simultaneously. All measured data would be serially transferred to a PC via RS232 before sending through the GSM modem. Through experiments, frequency and duty cycle responses are obtained to show that the proposed telecommunication system is robust and reliable.